Expression of the EspB Protein of Enteropathogenic Escherichia coli within HeLa Cells Affects Stress Fibers and Cellular Morphology - Taylor, Kathleen A. (American Society for Microbiology, 1999)
The EspB protein of enteropathogenic Escherichia coli (EPEC) is essential for the signaling events that lead to the accumulation of actin beneath intimately attached bacteria, a process that is known as the attaching and effacing effect. EspB is targeted to the host cell cytoplasm by a type III secretion apparatus. To determine the effect of intracellular EspB on the host cell cytoskeleton, we transfected HeLa cells with a plasmid containing the espB gene under the control of an inducible eukaryotic promoter. A HeLa cell clone that expressed espB mRNA and EspB protein after induction was selected for further study. The expression of EspB in these cells caused a dramatic change in cell morphology and a marked reduction in actin stress fibers. Cells expressing EspB were significantly impaired in their ability to support invasion by EPEC and Salmonella typhimurium. However, the expression of EspB within host cells could not compensate for the lack of EspB expression by an espB mutant strain of EPEC to restore attaching and effacing activity. These studies suggest that EspB is a cytoskeletal toxin that is translocated to the host cell cytoplasm, where it causes a redistribution of actin.